Anterior abdominal wall dermatofibrosarcoma protuberans: a case report - Ghimire, R; Subedi, S; Sharma, A; Bohara, Sandeep (Journal of Society of Surgeons of Nepal, 2016)
Dermatofibrosarcoma protuberans is a rare low-grade fibrohistiocytic tumor ,common in age group of 20 to 50 years. Histologically, it is diagnosed on the basis of a spindle-cell tumor arranged in small bundles in a characteristic cartwheel pattern. Though local recurrence rate is high, the treatment of choice is surgical resection with negative margins. We describe a case of a 34-year-old lady with dermatofibrosarcoma protuberans.